Construction of Cultural Identity of Lombok Society Through Ethno-Social Learning Models in School - Noor Fatmawati; Elya Umi Hanik; Islahuddin Islahuddin (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2026)
Social change has a major influence on the erosion of local cultural identity, so this study attempts to construct the cultural identity of the Lombok community through learning, which aims to explore the social and cultural values of the Lombok community that are integrated into learning at school. This field research uses a qualitative method with an ethnographic approach to understand a person's behaviour and experience based on their cultural environment. Data collection was carried out using interview with informants including: school principals, class teachers, and students using purposive sampling techniques. Next observations based on the experiences and behaviour of informants, and documentation. The integration of cultural, social, and religious values in the Elementary School at Lombok shows a harmonious synergy between local traditions and Islamic teachings. This approach not only strengthens students' understanding of the noble values of the Sasak community, but also helps them internalize religious teachings in their daily lives. Therefore, the sustainability of this model requires policy support, teacher training, and strengthening the synergy between the school and the local community.